Knowledge management processes and intellectual property management processes: an integrated conceptual framework (2017)
Intellectual property management, knowledge management are disciplines that have been treated independently, both in academia and in the organizational field. Through the legal discipline of intellectual property, the former manages intangible assets that are eligible for protection (copyright, patents and trademarks, among others) leaving aside those assets that cannot be realized in any way. The latter is devoted to the processes of knowledge management in general, namely, the knowledge of the processes, people, documents, etc. without any special status for protected knowledge. This article is the result of an exploratory research that has focused on the description of the design of a conceptual framework that integrates knowledge management processes and intellectual property processes, addressing both protected and unprotected knowledge. This research was carried out in two phases: a relationship with the documentary revision and the other with the definition and design of the proposed framework.